CONHEÇO, ENTENDO, LOGO CRIO: ARTE DIGITAL E AS NARRATIVAS SOBRE O PROCESSO CRIATIVO DOS ACADÊMICOS DO CURSO DE LICENCIATURA EM ARTES VISUAIS – UEPG - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
This paper was developed searching for answers about what are the priorities of students in the third year of Visual Arts Licentiate in UEPG during the process of learning and creation art by computer in a educational structure with an atmosphere when contradictions arising from material conditions, own social, economic, political and philosophical issues of each. To respond these concerns, the following objectives were elected: Identify the primary concepts of the Digital Art students from the third year of the Visual Arts Licentiate UEPG and their possible transformations, check the priority of academics regarding the design and implementation of Digital Poetics in their quest for understanding of creative essence, to ascertain whether the material conditions of academic and contradictions present in their conceptions of reality determines the realization of their productions, as well as understanding the production of academic computer via their gazes on Digital Poetics. To conduct the research was elected the method of dialectical materialism research, with contributions from: Marx (1998, 2003, 2005, 2007), Gamboa (2007), Abbagnano (1998), Jaeger (2001), Abraham (1999), Triviños (1987) and Malagodi (2010). Canclini (1984), Vazquez (1978) and Fischer (1976): Concerning the dialogue between art and the Critical Perspective authors were listed. For the concepts of Art, Technology, Digital Art and Poetry were chosen: Ferraz and Fusari (2001), Gombrich (1999), A. Nunes (2003, 2009, 2012), B. Nunes (2008), Cauquelin (2005) Janson (2001), Argan (2003, 2004), Bell (2008), Pareyson (2001), Marx (2007), Dubois (2004) Hunt (2003), Levy (2000), Becker (2009), Venturelli (2004, 2007), Prette (2009), Alpers (1999), Lieser (2009), Barros (2002) and Arantes (2005). Chose a qualitative approach, content analysis, and data were obtained by the tools: semi-structured questionnaire, digital diary and digital poetic memorial. An important tool of analysis was the table "3x3 matrix", drawn from the studies Baccon (2005, 2011) and Alvarez (2011). Under this view, amounted analysis categories and divisions of the stages of the studies that provided findings on the concepts of Digital Art, Digital Poetics, beyond the priorities of the subjects in the learning and digital art creation process. These understandings demonstrated, sometimes technical, sometimes learning and, most obviously, the intrinsic positions related expressions in the design of digital works. The evidence subsidized less apparent and closer reading of the essence of academics in their interactions with the computer designed in learning and creating digital art. Collaborating for a comprehensive look at the "Creative Digital Praxis".
Know, Understand, then Create: Digital Art and narratives about the creative process of students in the Visual Arts Licentiate UEPG
Keywords: tecnologia; Artes Visuais; arte digital; aprendizagem; poéticas; technology; visual arts; digital art; learning; poetics; CNPQ::CIENCIAS HUMANAS::EDUCACAO